Parametric study for epoxy loaded PMMA microcapsules using Taguchi and ANOVA methods - S. Sharma; V. Choudhary (eXPRESS Polymer Letters)
In this study, we systematically investigated the effect of various process parameters, such as surfactant concentration, core-to-shell ratio taken in the initial feed, temperature and agitation speed on the core content of microcapsules. For this study epoxy loaded poly(methyl methacrylate) microcapsules were prepared by solvent evaporation method. Taguchi orthogonal array with L25 matrix was implemented to optimize the experimental parameters for such microcapsules. The signal-to-noise ratio (SNR) and analysis of variance (ANOVA) were also performed to determine the optimum parameters and significance of various parameters. Morphological characterization (optical microscopy, scanning electron microscopy and transmission electron microscopy) and particle size analysis (mean particle size and particle size distribution) was done to investigate the effect of various parameters on the prepared microcapsules. SNR analysis identified the optimum levels of various parameters as: surfactant concentration- 10 wt%, core-to-shell ratio- 3:1, temperature- 40 °C and agitation speed- 300 rpm. ANOVA analysis showed that surfactant concentration was the most significant parameter in improving the core content of such microcapsules. The findings of Taguchi method were also verified with contour plots. Maximum core content obtained under optimum conditions was 63.53 wt% and such microcapsules can find applications for the development of self-healing polymer composites.